Analisis Efektivitas Refocusing Anggaran Pada Pemerintah Kota Malang Di Masa Pandemi Covid-19 - Ana Sopanah; Nerizqullah Auriga Tsarwa; Dwi Anggarani (Owner : Riset dan Jurnal Akuntansi, 2022)
Budget refocusing as an effort to accelerate the handling of the Covid-19 pandemic. However, this Budget Refocusing has not proven to be very effective in gaining public trust in the government in dealing with problems that arise during the Covid-19 pandemic. The purpose of this study is to analyze the effectiveness of budget refocusing in government. The research method used by researchers in this study is a qualitative method. The research design used by the researcher is a case study. The main research location chosen by the researcher is in Malang City, East Java Province. There are three data collection techniques used by researchers, namely observation, interviews, and documentation studies. While the data analysis techniques used include data collection, data reduction, data presentation, and drawing conclusions or verification. Then test the validity of the data and triangulate the data. From the results it can be concluded that the implementation of budget refocusing is realized by handling health, economic recovery and anticipation of regional economic decline. Efforts to reduce COVID-19 positive patients and improve economic growth have been carried out and are more effective. And the results of these implementations can create the effectiveness of Budget Refocusing due to improved economic growth and the reduced positive number of Covid-19 in Malang City.